Pengembangan Teknologi ERP Modul Customer Relationship Management Studi Kasus Rumah Makan Nasi Uduk “BABE” - Nurul Wahidah; Eka Prasetyaningrum; Lukman Bachtiar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The implementation of Enterprise Resource Planning (ERP) as one of the supports for the operation of an integrated business sector and better data accuracy. An ERP system consists of various modules and sub-modules that can represent certain business components, one of which is CRM. Application of Customer Relationship Management (CRM) or customer relationship management which is indirectly said to be computerizing customer data. This is intended so that the company knows what the needs and desires of customers are so that good relationships can be established with customers. In East Kotawaringin, there is now a place to eat called Rumah Makan Nasi Uduk